DETERMINAN TINGKAT PARTISIPASI ANGKATAN KERJA PEREMPUAN DI INDONESIA TAHUN 2015-2019 MENGGUNAKAN MODEL REGRESI DATA PANEL - Anggi Septiawan; Siti Haiyinah Wijaya (Politeknik Statistika STIS, 2020)
Female labor force participation rate (LFPR) in Indonesia is relatively smaller than male LFPR, in fact the difference is very far and never conical. In addition, the trend of female LFPR has stagnated at around 50 percent over the past decade. Therefore, this study aims to determine the determinants of female LFPR in Indonesia in 2015-2019. The analytical method used is inference analysis with panel data regression models. Fixed efffect model (FEM) with seemingly unrelated regression (SUR) method was chosen as the best model for estimating panel data regression models. The results of this study inddicate that higher mean years of schooling for women, female wage rate, manufacturing employment share, agricultural employment share, and gross regional domestic product at constants prices can increase the female LFPR in Indonesia. Meanwhile, the higher number of population taking care of households can reduce female LFPR in Indonesia.